INTEGRATING ENGLISH LANGUAGE SKILLS THROUGH READERS’ THEATRE TECHNIQUE FOR READING COMPREHENSION IN SECONDARY SCHOOLS IN KENYA - Kulo, Selina Alonya; Kibui, Agnes; Odundo, Paul (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2020)
Proficiency in reading skills requires a multifaceted technique which incorporates all English language skills. Techniques such as readers? theatre assimilates other language skills through adapting and performing scripts which engages learners actively in the reading process for fluency and comprehension. The study explored influence of integrating English language skills to enhance comprehension among learners in secondary schools through an intervention of readers? theatre technique. The study adopted socio constructivism in a quasi-experimental pretest posttest design. 426 form three learners and 19 teachers in Kisumu county participated in the study conducted within eight weeks. Participants? achievement in reading comprehension was measured using reading skills achievement test to ascertain effect of the intervention. The findings of the study, based on statistical analysis of t-test revealed participants in experimental groups performed better than those in control groups. The study revealed that engaging learners in adapting and performing scripts promoted active interaction with the text resulting in effective comprehension. The study concluded that incorporating language skills in the reading process creates a learner centered class and would be beneficial for enhancing reading comprehension. DOI: doi.org/10.24071/llt.2020.230102